A língua, pela enunciação, na escola (The language, by enunciation, at school) - Toldo, Claudia; Diedrich, Marlete Sandra (Estudos da Língua(gem), 2015)
Este artigo discute o ensino de língua portuguesa na escola, sublinhando o trabalho de texto em sala de aula e de como o sentido se constrói em cada sintagma organizado, possibilitando a arquitetura do nível semântico de um texto. Assim, no quadro da enunciação, registramos algumas posturas que devem ser adotadas para o estudo do texto em situação de sala de aula. O emprego das formas da língua aponta para uma construção, possível, do sentido de um texto. PALAVRAS-CHAVE: Enunciação. Texto. Sentido. Ensino de língua. ABSTRACT This article discusses the teaching of Portuguese language at school, underlining the work with texts in the classroom. Besides that, we examine how the meaning is built in each organized phrase, allowing the architecture of the semantic level of a text. Thus, in the context of enunciation, we bring out some propositions that should be adopted to the study of the text in the classroom situation. The use of language forms points to a possible text meaning construction. KEY-WORDS: Enunciation. Text. Meaning. Language Teaching.